Lowering inferred cluster magnetic field strengths: The radio galaxy contributions - Rudnick, L; Blundell, K (Institute of Physics Publishing, 2003)
We present a detailed examination of the relationship between the magnetic field structures and the variations in Faraday rotation across PK.S 1246-410, a radio source in the Centaurus cluster of galaxies, using data from Taylor, Fabian, and Alien. We find a significant relationship between the intrinsic position angle of the polarization and the local amount of Faraday rotation. The most plausible explanation is that most or all of the rotation is local to the source. We suggest that the rotations local to cluster radio galaxies may result either from thermal material mixed with the radio plasma, or from thin skins of warm, ionized gas in pressure balance with the observed galaxy or hot cluster atmospheres. We find that the contribution of any unrelated cluster rotation measure (RM) variations on scales of 2″-10″ are less than 25 rad m-2 the standard, although model-dependent, derivation of cluster fields would then lead to an upper limit of ≈0.4μG on these scales. Inspection of the distributions of rotation measure, polarization angle, and total intensity in 3C 75, 3C 465, and Cygnus A also shows source-related Faraday effects in some locations. Many effects can mask the signatures of locally dominated RMs, so the detection of even isolated correlations can be important, although difficult to quantify statistically. In order to use radio sources such as those shown here to derive cluster-wide magnetic fields, as is commonly done, one must first remove the local contributions. This is not possible at present.